Efektivitas Metode Pembelajaran Drill dengan Pendekatan Peer Teaching Ditinjau dari Minat dan Prestasi Belajar Matematika Siswa - Lalu Saparwadi (Didaktik Matematika, 2016)
The aim of this study was to investigate the effectiveness of drill teaching model with peer teaching approach compared to the conventional methods in terms of interest and achievement in learning mathematics student. Research type was design research for experiments that non-equivalent control group design. This study was conducted in SMAN 3 Selong, East Lombok district. The samples were 60 students consisting of experimental class and control class. After analyzing both descriptive and infrensi, it was found that drill learning model with peer teaching approach was effective in increasing the interest in mathematics learning and achievement. There were differences in the effectiveness of drill learning using peer teaching approach with conventional learning in terms of interest and achievement in learning mathematics student